STATUS AND ANALYSIS OF RISK DIVERSIFICATION IN COMMERCIAL BANKS - Saidov Ulugbek Abdivalievich (European Science Publishing, 2025)
The article examines the state and analysis of risk diversification in commercial banks, the main directions of risk diversification in commercial banks at the macroeconomic and microeconomic levels, the possibilities of reducing economic risk associated with risks in banks and preventing financial losses, and the application of the experience of foreign countries in our country.
Keywords: Commercial banks, risks, macro and microeconomic level, monetary policy, bank credit, risk management, risk diversification, bank loan portfolio.